Critical scapula motions for preventing subacromial impingement in fully-tethered front-crawl swimming - Du, T.; Yanai, T. (Sports Biomechanics, 2022)
The aims were to quantitatively describe the coordinated motions of the scapula and humerus during fully tethered front-crawl strokes and to test the hypothesis that scapular motion functions to reduce the risk of subacromial compression. An electromagnetic tracking device was used to record the kinematics of the thorax, humerus, and scapula on the dominant side in 17 collegiate swimmers. Because evidence suggests that compressive force develops under the coracoacromial arch when the arm elevated above 90º of arm elevation is maximally internally rotated, such shoulder configurations were measured for each participant. A series of scapulohumeral angles measured with this procedure were compared with the corresponding angles exhibited during fully tethered front-crawl swimming to identify the scapulohumeral angles indicative of subacromial compression. Additional comparison was performed without taking the scapular motion into account. Scapulohumeral angles indicative of subacromial compression were observed in 15 participants, accounting for 7.7 ± 7.1% of stroke cycle time. This duration was significantly less than the corresponding duration identified without having taken the scapular motion into account (22.6 ± 13.8% of stroke cycle time). The difference was due primarily to the unique movements of the scapular to accommodate demands imposed by stroke motions, and this supported the hypothesis.